2006
DOI: 10.1007/s00705-006-0862-4
|View full text |Cite
|
Sign up to set email alerts
|

Co-circulation of distinct genetic lineages of astroviruses in turkeys and guinea fowl

Abstract: Viruses belonging to the genus Astrovirus have been increasingly associated with enteritis in mammalian and avian species, including turkeys. More recently, astroviruses have also been detected in diseased guinea fowl. In turkeys, two genetically distinct types of astrovirus have been reported, namely turkey astrovirus 1 and 2 (TAstV1 and TAstV2). The prevalence and the pathogenesis of astrovirus infections in this species is currently unknown, with the exception of data generated in the USA. In the present re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
47
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 20 publications
5
47
0
1
Order By: Relevance
“…Two genetically distinct viruses were used in this study: one TAstV2 (TK-6363) detected in 2003 in a commercial turkey farm (Cattoli et al, 2007); and one GFAstV (GF-5497), detected in 2009 in a commercial guinea fowl farm in Italy. Birds in these farms showed depression, severe enteritis and increased mortality (up to 30%), and from both farms the laboratory diagnosis of astrovirus infection was made based on electron microscopy examinations and confirmed by astrovirus-specific reverse transcriptase-polymerase chain reaction (RT-PCR) performed as previously described (Cattoli et al, 2007). Based on the phylogenetic analysis of the ORF1b sequence, the turkey virus TK-6363 and the guinea fowl virus GF-5497 are grouped into two separate clusters according to the distinction made by Cattoli et al (2007).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Two genetically distinct viruses were used in this study: one TAstV2 (TK-6363) detected in 2003 in a commercial turkey farm (Cattoli et al, 2007); and one GFAstV (GF-5497), detected in 2009 in a commercial guinea fowl farm in Italy. Birds in these farms showed depression, severe enteritis and increased mortality (up to 30%), and from both farms the laboratory diagnosis of astrovirus infection was made based on electron microscopy examinations and confirmed by astrovirus-specific reverse transcriptase-polymerase chain reaction (RT-PCR) performed as previously described (Cattoli et al, 2007). Based on the phylogenetic analysis of the ORF1b sequence, the turkey virus TK-6363 and the guinea fowl virus GF-5497 are grouped into two separate clusters according to the distinction made by Cattoli et al (2007).…”
Section: Methodsmentioning
confidence: 99%
“…A genetically and antigenically distinct type of turkey astrovirus was then identified in 1996 (Turkey astrovirus type 2 [TAstV2]) by Koci et al (2000a). Since these first detections, enteritis in turkey has been increasingly associated with the presence of astroviruses (Cattoli et al, 2007;Pantin-Jackwood et al, 2007, 2008aDa Silva et al, 2008;Jindal et al, 2010a), although high astrovirus prevalence has also been reported in apparently healthy turkey flocks (PantinJackwood et al, 2007(PantinJackwood et al, , 2008aJindal et al, 2010b;Domanska-Blicharz et al, 2011). TAstV2 appears to be the most common among the identified turkey astroviruses, while TAstV1 and avian nephritis virus* an astrovirus first described as responsible for nephritis in chicken (Imada et al, 2000)*have only been detected sporadically in turkey flocks (Pantin-Jackwood et al, 2007, 2008aDomanska-Blicharz et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations